Effects of anterior weight-shifting methods on sitting balance in wheelchair-dependent patients with spinal cord injury - Ahn, Jeoungah; Min, Dong-Ki; Choe, Han Seong (Journal of Physical Therapy Science, 2018)
[Purpose] This study aimed to compare changes in the center of pressure between healthy subjects and patients with spinal cord injury and to provide basic information to these patients for improving their sitting balance. [Subjects and Methods] A total of 12 healthy subjects without histories of neurological or psychiatric disorders and 12 patients with spinal cord injuries were recruited. In all subjects, a change in the center of pressure during the performance of the modified functional reach test was measured using a Force Sensing Array system while the subjects were seated in a wheelchair. In the spinal cord injury group, the change in the center of pressure was highest when subjects reached forward while holding a gym ball. [Results] In the spinal cord injury group, the change in the center of pressure was highest when subjects reached forward while holding a gym ball. A significant correlation between forward reaching of the upper limbs with shoulders at 90° flexion and a change in the center of pressure was found. [Conclusion] Our findings suggest that the combination of functional reaching and the change in the center of pressure assessment is novel enough to be attempted to achieve sitting balance control in patients with spinal cord injury. The findings can provide clinical interventions that contribute to the improvement in the balance ability of wheelchair-dependent individuals.